Development of a multiplex PCR method for detection of Pasteurella multocida and Mannheimia haemolytica - Nguyễn, Thị Thu Thảo; Nguyễn, Văn Phú; Nguyễn, Hữu Thọ; Nguyễn, Thị Oanh; Trương, Phúc Hưng; Hồ, Thị Xuân Túy; Nguyễn, Xuân Huy; Lê, Công Tuấn; Nguyễn, Thị Thịnh; Nguyễn, Thị Kim Cúc (Hue University Journal of Science: Natural Science, 2023)
The multiplex PCR assay has been used to diagnose different diseases in livestock in Vietnam; however, this method has not been well-applied to sheep diseases. This study developed a multiplex PCR assay to detect the two main agents, Pasteurella multocida and Mannheimia haemolytica, causing Pasteurellosis in sheep. By using two pairs of specific primers, with the optimum concentration of each primer being 5 pM, this method successfully amplified the kmt1 gene from P. multocida and the gcp gene from M. haemolytica in the same reaction containing DNA of P. multocida and M. haemolytica at the lowest concentration of 0.1 ng each. Moreover, this multiplex PCR reaction is not affected by the artificial presence of some other bacterial DNA. In particular, this multiplex PCR showed 100% confidence in a stability test on a small scale with 20 raw DNA samples obtained from direct heat treatment or enrichment before heat treatment of 10 field samples. This is the first study in Vietnam on diagnosing P. multocida and M. haemolytica by multiplex PCR. This method is valuable for detecting P. multocida and M. haemolytica in sheep and serves as a reference for detecting these bacteria in other household animal.